Fracture processes observed with a cryogenic detector - Astrom J.; Stefano P.C.F. Di; Proebst F.; Stodolsky L.; Timonen J.; Bucci C.; Cooper S.; Cozzini C.; Feilitzsch F.v.; Kraus H.; Marchese J.; Meier O.; et al. (2006, 2006)
Title screen